Natural Spillover Risk and Disease Outbreaks: Is Over-Simplification Putting Public Health at Risk? - David Bell; Jean von Agris; Blagovesta Tacheva; Garrett Wallace Brown (Journal of Epidemiology and Global Health)
Abstract The pandemic prevention, preparedness and response (PPPR) agenda is currently dominating international public health. International agencies including the World Health Organization and World Bank are proposing an unprecedented level of funding that will inevitably have broad consequences across health and society. Arguments supporting pandemic policy are heavily based on the premise that pandemic risk is rapidly increasing, driven in particular by passage of pathogens from animal reservoirs to establish transmission in the human population; ‘zoonotic spillover’. Proposed drivers for increasing spillover are mostly based on environmental change attributed to anthropogenic origin, including deforestation, agricultural expansion and intensification, and changes in climate. Much of the literature, including reports published by international agencies and peer-reviewed papers, offers support for fundamental changes in public health policy premised on definitive statements that spillover is indeed increasing, that underlying anthropogenic drivers are the main reason for this, and that these are remediable. However, many of these assumptions are poorly supported by cited literature, over-simplifying a highly complex set of ecological interactions. This picture is further complicated by rapidly and unevenly evolving capacity for pathogen detection and notification. Public health policy based on incorrect assumptions and overly simplified analyses is likely to lead to poorly designed interventions and poor outcomes. If we are to deal effectively with outbreak risk within the broad context of competing public health priorities, there is an urgent need to re-evaluate current assumptions on drivers of outbreaks based on available evidence and address continuing major gaps in knowledge.